Analisis Pengamatan Ekosistem Perairan Tergenang - Waruwu, Julpin carles; Harefa, Meserius (Jurnal Perikanan dan Kelautan, 2025)
The study of stagnant freshwater ecosystems aims to identify and understand the characteristics of non-flowing aquatic environments such as rice fields, swamps, and ponds. This practicum was conducted in Hilimbowo Olora Village and involved observations of physical parameters (color, odor, substrate), biotic components (vegetation and fauna), as well as the identification of plant and animal species present. Observations showed that the water was clear and odorless, with a substrate composed of mud. The dominant vegetation included rice and water spinach, while the observed fauna consisted of panchax fish, golden apple snails, and freshwater crabs. This study highlights the importance of interactions between abiotic and biotic components in maintaining ecosystem balance. Additionally, the practicum provided students with hands-on experience in observing, analyzing, and classifying aquatic organisms based on morphological characteristics. Thus, this activity contributes to enhancing students’ understanding and ecological awareness of the importance of conserving aquatic ecosystems.